2004
DOI: 10.1097/01.mnm.0000126516.57329.07
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 166Dy/166Ho-EDTMP: a potential in vivo generator system for bone marrow ablation

Abstract: The prepared radiolabelled EDTMP has adequate properties as a stable in vivo generator system for bone marrow ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…As a comparable 166 Ho bone pain palliation agent, 166 Ho-EDTMP has been proposed as a potential clinically used radiopharmaceutical by different groups [7,10]. A low liver uptake has been reported for 166 Ho-EDTMP which is considered a disadvantage as a bone pain palliative agent leading to less unwanted liver dose in patients (Fig.…”
Section: Biodistribution Of 166 Ho Cation and 166 Ho-pmd In Wild-typementioning
confidence: 96%
See 1 more Smart Citation
“…As a comparable 166 Ho bone pain palliation agent, 166 Ho-EDTMP has been proposed as a potential clinically used radiopharmaceutical by different groups [7,10]. A low liver uptake has been reported for 166 Ho-EDTMP which is considered a disadvantage as a bone pain palliative agent leading to less unwanted liver dose in patients (Fig.…”
Section: Biodistribution Of 166 Ho Cation and 166 Ho-pmd In Wild-typementioning
confidence: 96%
“…The use of bisphosphonates has made a significant change in the therapeutic approach to management of bone metastasis and pain prevention in breast cancer and multiple myeloma [4]. Various therapeutic 166 Ho bone-seeking agents have been reported such as 166 Ho-DOTMP [5,6], 166 Ho-EDTMP [7,8], 166 Ho-AP-DDMP [9], as well as 166 Dy/ 166 Ho-EDTMP demonstrating adequate properties as a stable in vivo generator system for bone marrow ablation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Different phosphonate complexes have been labelled with [ 166 Ho]holmium targeting bone and bone marrow lesions [ 111 , 112 , 113 , 114 ]. [ 166 Ho]holmium is an inexpensive β¯-emitter, majorly used in the treatment of multiple myeloma [ 112 , 115 ].…”
Section: [166 Ho]holmium-ethylene Diamine Tetramethylene Phosphonmentioning
confidence: 99%
“…In a pilot study, [ 166 Ho]Ho–DOTMP was used for the treatment of bone metastases in breast cancer patients showing median time to progression of 10.4 months [ 118 ]. In addition, owing to the remarkably higher radiation dose to the bone marrow, combination of [ 166 Dy]dysprosium/[ 166 Ho]Ho-EDTMP is proposed as an agent for bone marrow ablation [ 113 ].…”
Section: [166 Ho]holmium-ethylene Diamine Tetramethylene Phosphonmentioning
confidence: 99%
“…Animal studies showed a fast blood clearance of [ 166 Dy]Dy/[ 166 Ho]Ho EDTMP and a skeletal uptake of 22.32 ± 1.86% ID/g at 2 h and 20.12 ± 1.94% ID/g after 10 days. Theoretical bone marrow absorbed dose calculations indicate that the [ 166 Dy]Dy/[ 166 Ho]Ho EDTMP in vivo generator system produced 3.47 times more dose than [ 166 Ho]Ho DOTMP per unit of initial activity in the skeleton (Pedraza-Lopez et al 2004a). The same group also demonstrated that the [ 166 Dy]Dy/[ 166 Ho]Ho EDTMP system induced considerable cytotoxicity, genotoxicity and severe myelosuppression in mice at bone marrow absorbed doses of 18–23 Gy, suggesting that this system could potentially be a good agent for use in humans (Pedraza-Lopez et al 2004b).…”
Section: Intravenous Applicationsmentioning
confidence: 99%